The influence of culture on Finnish corporate leaders : Perceptions of current and future leaders - Viljanen, Mikael (My University, 2022)
One of the key challenges in international business is the incompatibility between different cultures. Therefore, getting new and up to date knowledge about different cultures is important. This study aims to provide further knowledge about Finnish culture by researching about what are perceived to be the most important business goals for Finnish corporate leaders, or in other words, which aspects Finnish corporate leaders prioritize when doing business. This study aims to provide both the perspective what are the most important business goals for current corporate leaders, but also what seem to be the most important business goals of the future Finnish corporate leaders. There is already a lot of extensive research about the characteristics of Finnish culture, through the research of cultural dimensions. However, the perspective about the most important business goals of Finnish corporate culture was yet to be discovered. This study allows to both provide new information about Finnish culture in this regard but also allows to test existing theory about Finnish culture, whether the current knowledge of Finnish culture in cultural dimensions theories align with the findings of this study. This study conducted a survey that was conducted to degree students at Turku School of Economics and asked the students to rank the importance of different business goals to themselves and how they perceive current Finnish corporate leaders to rank the importance of these business goals. The 15 different business goals used in this study were the same as in Geert Hofstede’s cross-cultural study about business goals. This allows to easily compare the results in this study to earlier research. The students at Turku School of Economics were used as participants because they allow to provide the aspect about future Finnish corporate leaders, as it is expected that some of the students at TSE may be some of the future Finnish corporate leaders. The findings in this study indicate that compared to international averages in Hofstede’s study, current Finnish corporate leaders value highly ethical business goals, such as responsibility towards employees, responsibility towards society, following ethical norms and staying within the law. Meanwhile personal wealth or power of the corporate leader are perceived less important for current Finnish corporate than the international averages. For the students at Turku School of Economics, responsibility towards society was a very highly valued business goal, at least compared to the international averages. These findings in many ways align with earlier theory about Finnish culture. Finnish culture is considered quite feminine, which means Finnish culture is considered to value the idea of taking care of everyone over competitiveness and personal success. The idea of putting high importance on responsibility towards society also aligns with the previous finding that Finnish culture is considered very universalistic.
Keywords: cross-cultural management, cultural differences, business goals, values, corporate social responsibility, responsible leadership, Finland